Henry Clay and His Political Role in the History of the United States (1777-1852) - صالح جاسم امل (Al-Adab Journal, 2018)
This study covers the life of Henry Clay, one of the most important and influential figures in the American history. The study sheds light on his birth, growing up, education and work as an attorney in Virginia State after obtaining a law practice license in 1797. His work as an attorney shaped his professional and political character. In 1799, Clay got married, and that made him settle in Kentucky State. After that, he worked at the State Council and represented the State in Congress for the Republican-Democratic Party in 1803. He played a great role in passing laws that supported the United States independence in political and economic areas, and in solving the slavery problems in the United States by taking part in the First Missouri Compromise (1820). He further supported the US economy through his role in renewing the National Bank license in 816 and 1836. Finally, he contributed to the Second Missouri Settlement (1850).